Pengaruh Prokrastinasi, Integritas dan Motivasi Belajar Terhadap Kecurangan Akademik (Studi pada Mahasiswa Akuntansi Universitas Islam Malang) - Muawanah Muawanah; Maslichah Maslichah; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of procrastination, integrity and learning motivation on academic cheating. The population in the study is active undergraduate students of the Accounting Study Program, Faculty of Economics and Business, Islamic University of Malang, class of 2019 and 2020 with a sample of 200 respondents. Data analysis techniques used in this research is multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study it can be seen that: (1) procrastination has a positive effect and has a significant effect on academic cheating, where a regression coefficient of 3.589 is obtained and sig 0.000. (2) Integrity has a significant positive effect on academic cheating, where obtained a regression coefficient of 5.646 and sig 0.000. (3) owned learning motivation has a significant positive effect on academic cheating, where a regression coefficient of 3.408 is obtained and sig 0.001. The magnitude of the influence of independent variables on academic cheating. Suggestions for future researchers are to add research locations because it would be better if the samples taken involved more respondents.Keyword : Procrastination, integrity, motivation, and academic and academic fraud